Stabilization of T-S fuzzy asynchronous Boolean control networks with time delay under noise - Feifei Yang; Yujie Sun; Chuan Zhang; Xianghui Su; Hao Zhang (Scientific Reports)
Abstract This paper mainly investigates the stabilization problem of Takagi-Sugeno (T-S) fuzzy asynchronous Boolean control networks (ABCNs) under aperiodic sample-data state-feedback control. First, the system has been converted into a discrete time-delay system by using the theory of the semi-tensor product for matrices. After that, algebraic forms of the augmented ABCNs are obtained. Second, the stabilization of T-S fuzzy ABCNs with fixed time delay is researched. Based on that, noise is further considered in the time delay of ABCNs and the fixed time delay is altered to the unfixed case. Then, sufficient and necessary conditions for proposed stabilizations are derived by using different approaches. Ultimately, examples are provided to demonstrate the effectiveness and superiority of achieved results.